Integrated Alzheimer's Disease Rating Scale: Clinically meaningful change estimates. Issue 1 (6th June 2022) - Wessels, Alette M.; Rentz, Dorene M.; Case, Michael; Lauzon, Steve; Sims, John R.
Abstract: Introduction: The Integrated Alzheimer's Disease Rating Scale (iADRS) has been used to detect differences in disease progression in early Alzheimer's disease (AD). The objectives of this study were to enhance understanding of iADRS point changes within the context of clinical trials, and to establish a minimal clinically important difference (MCID) on the iADRS. Methods: Data from AMARANTH and EXPEDITION3 were analyzed using various approaches, including anchor‐based, distribution‐based, regression analyses, and cumulative distribution function (CDF) plots. Three potential anchors were examined, including the Clinical Dementia Rating—Sum of Boxes, Mini‐Mental State Examination, and Functional Activities Questionnaire. Triangulation of all results was used to determine the MCID for participants with mild cognitive impairment (MCI) due to AD and AD with mild dementia. Results: All three anchors met criteria for "sufficiently associated" (|r| = 0.4–0.7). Cumulatively, results from anchor‐based and distribution‐based results converged to suggest an iADRS MCID of 5 points for MCI due to AD and 9 points for AD with mild dementia. Regression analyses and CDF plots supported these values. Discussion: These findings suggest the iADRS can be used in clinical trials to detect a clinically meaningful outcome of AD progression.